2009
DOI: 10.1007/s00024-009-0485-2
|View full text |Cite
|
Sign up to set email alerts
|

Common Evolution of Mechanical and Transport Properties in Thermally Cracked Westerly Granite at Elevated Hydrostatic Pressure

Abstract: Increasing the damage and crack porosity in crustal rocks can result in significant changes to various key physical properties, including mechanical strength, elastic and mechanical anisotropy, and the enhancement of transport properties. Using a Non-Interactive Crack Effective Medium (NIC) theory as a fundamental tool, we show that elastic wave dispersion can be inverted to evaluate crack density as a function of temperature and is compared with optically determined crack density. Further, we show how the exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 42 publications
6
42
0
Order By: Relevance
“…Permeability was either (i) measured (black symbols) as a function of P eff (hence increasing p f ) on the microcracked Fo3 sample, the "intact" Fo7, and the microcracked WGs at lowest P eff = 1 MPa or (ii) attained (red symbols) from published works (Delle Piane et al, 2015;Loaiza et al, 2012;Nasseri et al, 2009). In the relevant frequency range, we measured extreme values of V p /V s in crustal rocks of very different mineralogical composition, hence very different matrix Poisson's ratio.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Permeability was either (i) measured (black symbols) as a function of P eff (hence increasing p f ) on the microcracked Fo3 sample, the "intact" Fo7, and the microcracked WGs at lowest P eff = 1 MPa or (ii) attained (red symbols) from published works (Delle Piane et al, 2015;Loaiza et al, 2012;Nasseri et al, 2009). In the relevant frequency range, we measured extreme values of V p /V s in crustal rocks of very different mineralogical composition, hence very different matrix Poisson's ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The thermal treatment method was shown to induce a large and isotropic degree of microfracturing due to the mismatch in thermal expansion of the grains in initially isotropic rocks (Fredrich & Wong, 1986;Nasseri et al, 2007Nasseri et al, , 2009). The thermal treatment method was shown to induce a large and isotropic degree of microfracturing due to the mismatch in thermal expansion of the grains in initially isotropic rocks (Fredrich & Wong, 1986;Nasseri et al, 2007Nasseri et al, , 2009).…”
Section: Rock Samplesmentioning
confidence: 99%
“…In order to account for this discrepancy, we regarded the thermal expansivities of our damaged mineral phases as free fitting parameters and reduced them empirically until our numerical experiment matched the radial deformation history of the physical experiment (see below). Intracrystalline damage also lowers the elastic moduli of the affected minerals and thereby internal stresses [Heard and Page, 1982;Nasseri et al, 2009]. However, we lumped this effect solely into the downscaling of thermal expansivities for two reasons: first, Bruner [1984] demonstrated that, in quartzo-feldspathic rocks, thermal-expansion mismatch makes the main contribution to internal stresses for geologically reasonable geotherms; second, the degrees of freedom in the numerical calibration are reduced.…”
Section: Calibration Of the 2d Numerical Experimentsmentioning
confidence: 99%
“…Hitherto, thermal-elastic internal stresses were mainly investigated in the context of cooling brittle rocks, for three reasons. First, they can generate micro-cracks (Figure 1) in the upper $4 km of the continental crust [e.g., Heard and Page, 1982], which affect rock properties such as elasticity, strength, fracture toughness, thermal conductivity, and permeability [Cooper and Simmons, 1977;Meredith and Atkinson, 1985;Nasseri et al, 2009]. This is relevant for resource extraction (e.g., mining, quarrying, and drilling), nuclear waste disposal, and reservoir stimulation [Heard and Page, 1982;Nasseri et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Very often, polyhedron-type samples such as octadecahedrons, tetratrioctahedrals [12][13][14] and/or cubes with beveled edges [15,16] are used. Cylindrical samples are mostly used to determine elastic anisotropy [17][18][19][20] and other quantities as well.…”
Section: Introductionmentioning
confidence: 99%